2021
DOI: 10.1073/pnas.2107289118
|View full text |Cite
|
Sign up to set email alerts
|

Tardigrades exhibit robust interlimb coordination across walking speeds and terrains

Abstract: Tardigrades must negotiate heterogeneous, fluctuating environments and accordingly utilize locomotive strategies capable of dealing with variable terrain. We analyze the kinematics and interleg coordination of freely walking tardigrades (species: Hypsibius exemplaris). We find that tardigrade walking replicates several key features of walking in insects despite disparities in size, skeleton, and habitat. To test the effect of environmental changes on tardigrade locomotor control circuits we measure kinematics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 42 publications
10
20
0
Order By: Relevance
“…Locomotion speed is a function of the frequency and length of a cycle. We found that, similar to previous findings, the speed of larval crawling is determined more so by stride frequency than stride length (Frigon et al, 2014; Grillner et al, 1979; Jacobson and Hollyday, 1982; Nirody et al, 2021). Furthermore, similar to limbed animals including mammals and other insects, the two constituent phases of a locomotor cycle vary differentially with speed, with the interwave phase varying more than the wave phase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Locomotion speed is a function of the frequency and length of a cycle. We found that, similar to previous findings, the speed of larval crawling is determined more so by stride frequency than stride length (Frigon et al, 2014; Grillner et al, 1979; Jacobson and Hollyday, 1982; Nirody et al, 2021). Furthermore, similar to limbed animals including mammals and other insects, the two constituent phases of a locomotor cycle vary differentially with speed, with the interwave phase varying more than the wave phase.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, limbed animals change the frequency of walking by varying the locomotor cycle differentially: the stance phase is varied, but the swing phase is almost unchanged, even as animals switch to different gaits. This holds true for animals ranging from insects and tardigrades to mammals (Boije and Kullander, 2018;Frigon et al, 2014;Grillner et al, 1979;Jacobson and Hollyday, 1982;Nirody et al, 2021). How the nervous system generates this asymmetry in the variation of stance and swing phases is still an open question (Bidaye et al, 2018;Boije and Kullander, 2018;Kiehn, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the robots in this work is presently the fastest submillimeter robot that can be actuated remotely and move continuously on nonspecialized surfaces. It is faster than some micro­organisms such as Caenorhabditis elegans ( C. elegans ) and Tardigrade of this size, and even comparable to the speed of Paramecia and some arthropods in the Formicidae family. , …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, microrobots with fast speed enable them with more application potential for practical scenarios. Figure shows the comparison of relative speeds with respect to body length including several arthropods and microorganisms (green), the set of most advanced optical actuated microrobots (orange), ,,, , inchworm-type microrobots (blue), ,, and this work (red stars). Among inchworm-type microrobots, the microrobots in this work have the smallest size and can operate at a relatively fast speed (3.66 BL/s).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, most of the tardigrades would be dispersed on the second day post‐ingestion that is, on average 1 m (maximum 10 m) away from their original location. On a smooth, wet, two‐dimensional surface in laboratory conditions, tardigrades were reported to move at speeds between 1.98 and 15.81 mm/min (Li & Wang, 2005 ; Nirody et al, 2021 ). Hence, theoretically, at directed higher speed movement, tardigrades could match, or even exceed, the distance traveled by a snail (e.g., 48 h at 15.81 mm/min = 45.5 m).…”
mentioning
confidence: 99%